2020
DOI: 10.3390/ijerph17197139
|View full text |Cite
|
Sign up to set email alerts
|

Taste and Health Information on Fast Food Menus to Encourage Young Adults to Choose Healthy Food Products: An Experimental Study

Abstract: Currently, a great number of people have an unhealthy dietary intake, leading to chronic diseases. Despite the high prevalence of obesity and people being overweight, only a few strategies to promote healthier food products have been proven effective. Therefore, the objective of this study was to test the effect of the presence of health information and its integration into a fast food menu context on young adults’ healthy food choices. An experimental between-subjects design consisting of three conditions—sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Indeed, many resources are already poured into communication campaigns aimed at chefs. However, these campaigns should go into more depth on the health benefits of consuming olive oils, with explicit messages [ 51 ] and health claims related to reducing disease risks, rather than functional claims [ 27 ]. The pairing of health professionals and chefs should be potentiated in these campaigns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many resources are already poured into communication campaigns aimed at chefs. However, these campaigns should go into more depth on the health benefits of consuming olive oils, with explicit messages [ 51 ] and health claims related to reducing disease risks, rather than functional claims [ 27 ]. The pairing of health professionals and chefs should be potentiated in these campaigns.…”
Section: Resultsmentioning
confidence: 99%
“…Thirdly, restaurants that seek to stand out from the crowd can find “healthy eating” as an effective strategy for market positioning and differentiation, given that consumers value health above all else in their food choices. Indeed, previous studies have demonstrated that health claims drive greater consumption of healthy foods [ 27 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, according to a study in Aleppo, higher education students requested meals with significantly lower energy values when opting for menu items with nutritional information compared to menus without this information [31]. Another more recent study showed that individuals who received direct information about healthy options present on fast food menus showed a greater tendency to select healthier food products compared to those exposed to more discreet integrated health information [32].…”
Section: Discussionmentioning
confidence: 99%
“…These foods are characterized by being rich in fat, sugar and salt which makes them more palatable and tastier than vegetables. This perception of vegetables being less tasty than other foods may be explained by earlier experience or lack of experience with vegetables [ 59 ]. As food choices are mainly determined by the perceived tastiness of food products, providing vegetable tasting opportunities to young people from socioeconomically disadvantaged backgrounds at an early age may have a positive effect on their acceptance and may encourage their selection among this population group [ 59 61 ].…”
Section: Discussionmentioning
confidence: 99%